A panel cointegration study of the Euro effect on trade - Christian Gengenbach (Verein für Socialpolitik, 2010)
Bun and Klaassen (2007) investigate the impact of the introduction of Euro on bilateral trade. Accounting for deterministic trends in the residuals of the gravity equation they estimate an Euro effect of about 3%, smaller than previous estimates in the range of 5% to 40%. In this paper we revisit their data using methods recently advanced in the analysis of non-stationary panel data with cross-sectional dependence. Using several panel unit root tests we find strong evidence that (the log of) bilateral trade, as well as the product of GDP and GDP per capita have unit roots. However, we find cointegration between these variables using the cointegration test of Gengenbach, Palm and Urbain (2006) and the error correction tests proposed by Gengenbach, Westerlund and Urbain (2008). Employing the common correlated effects (CCEP) estimator of Pesaran (2006) and the continuously updated (CUP) estimator of Bai, Kao and Ng (2009), we obtain estimates of the cointegrating vector and estimates of the Euro effect on bilateral trade. Our estimates vary between models and estimators but seem to support the findings of Bun and Klaassen (2007).
Keywords: C23; F15; F33; 330; Gravity models; trade; panel cointegration; common factors